Assessment of Use Values and Propagation Methods of Native Fodder and Fruit Species in Merhabete District, Ethiopia - Getachew, Goremsu (Indonesian Journal of Environmental Management and Sustainability, 2023)
Native fodder and fruit species provide various products and services to local communities besides their fruit (food) and fodder supply in our country including in the study area. Although, there is rich traditional knowledge on propagation methods of native fodder and fruit species and their local use, but little recognition has been given by forestry research and extension efforts to enhance them. The general objective of the study was to investigate the use value and propagation methods of native fodder and fruit species in the Merhabete district, Ethiopia. A total of 127 households were randomly selected and interviewed about local use and propagation methods of native fodder and fruit species. The study indicated that the majority of native fodder and fruit species were used for firewood (23.9%) followed by charcoal (10.9%), timber, and construction wood (10.6%), fencing (9.3%), soil fertility improvement (9.1%), farm tool (7.1%), and medicine (3.3%). Native fodder and fruit species (42.7%) were propagated through wilding (natural regeneration) and the remainder were propagated through seedlings (7.2%), seed (6.06%), and stem cutting (4.8%). Overgrazing (46.5%) followed by overexploitation (22%), climate change/drought (20.5%), and disease and pest (11%) were the major regeneration constraints to native fodder and fruit trees/shrubs species in the study area. Therefore, proper involvement either through research or development works are essential to reduce the propagation constraint of studied species. Ziziphus spina-christi (L.) Desf. followed by Faidherbia albida (Delile) A. Chev., Cordia africana Lam., Ximenia americana L., and Acacia senegal (L.) Willd. were the most preferred species for planting by farmers in the study area. Domestication should focus on the preferred top five species to promote species conservation and sustainable use.